Gamification — the Way of Motivation or Way of Control over the Labor Process? - Elena Tсyplakova (Journal of Economic Sociology, 2016)
The paper presents results of sociological research that analyzed the new way of controlling the labor process — gamification. This study was based on a concept of post-Fordism and neo-Fordism and focused on examining a combination of the game elements for motivation and electronic surveillance. According to industrial sociology traditions, special attention was paid to strengthening control over workers and social and labor conflicts.This research was based on data from 16 semi-structured interviews with the managers and employees of a Russian company that produces alcoholic beverages. Data analysis was made using the principles of grounded theory. As a result, one positive of introducing gamification was the successful combination of the virtual system and the workers’ desire to win, which promoted the employees’ increased involvement in the labor process. In general, introducing gamification didn't lead to open conflicts between the managers and workers; however, changes in the organization of the labor process and technical difficulties instigated passive ways of resisting new working conditions. Deterioration of the social climate was collective because the aggravated competition between workers also led to negative consequences. As a result, it was revealed that although gamification is positioned as a motivator, in reality, it is primarily a way to exert total control over the labor process, which is organized by automatic operations and electronic monitoring. A distinctive feature of this method is the use of gaming elements to vary routine activities and disguise negative aspects in the whole mechanism.